2010
DOI: 10.1152/ajpregu.00754.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced systolic pressure load decreases cell-cycle activity in the fetal sheep heart

Abstract: The fetal heart is highly sensitive to changes in mechanical load. We have previously demonstrated that increased cardiac load can stimulate cell cycle activity and maturation of immature cardiomyocytes, but the effects of reduced load are not known. Sixteen fetal sheep were given either continuous intravenous infusion of lactated Ringer solution (LR) or enalaprilat, an angiotensin-converting enzyme inhibitor beginning at 127 days gestational age. After 8 days, fetal arterial pressure in the enalaprilat-infuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…If the maturation is completed before the appropriate number of myocytes is achieved, the heart development could be compromised at birth with fewer myocytes. It has been shown that thyroid hormone (4), atrial natriuretic peptide (30), experimental reduction in systolic pressure (29), and fetal hypoxia induced by placental restriction (22,27) reduce the number of cardiomyocytes in the fetal sheep heart. Similar findings were obtained in rats, showing that gestational hypoxia decreased cardiomyocyte proliferation and increased the percentage and size of binucleated myocytes in fetal hearts (1,38), indicating an early morphology of cardiomyocyte hypertrophy (6).…”
Section: Discussionmentioning
confidence: 99%
“…If the maturation is completed before the appropriate number of myocytes is achieved, the heart development could be compromised at birth with fewer myocytes. It has been shown that thyroid hormone (4), atrial natriuretic peptide (30), experimental reduction in systolic pressure (29), and fetal hypoxia induced by placental restriction (22,27) reduce the number of cardiomyocytes in the fetal sheep heart. Similar findings were obtained in rats, showing that gestational hypoxia decreased cardiomyocyte proliferation and increased the percentage and size of binucleated myocytes in fetal hearts (1,38), indicating an early morphology of cardiomyocyte hypertrophy (6).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cardiomyocyte PCNA staining remains elevated, suggesting cellular proliferation despite lack of gross cardiac hypertrophy (Sandgren et al 2015). Chronic blockade of ACE inhibits fetal cardiac proliferative growth, although interpretation of this effect is complicated by dramatically lowered arterial pressure (O’Tierney et al 2010). The findings of these studies taken together suggest that the primary effect of AII on cardiomyocyte growth in utero is a result of altered systemic arterial pressure load.…”
Section: Regulatory Signals Associated With Birthmentioning
confidence: 99%
“…Reduced near-term fetal systemic arterial pressure similarly inhibits cardiomyocyte proliferation and cardiac growth (Norris et al 2014; O’Tierney et al 2010). Increased preload in chronic fetal anemia may contribute to the increased cardiomyocyte proliferation, terminal differentiation and enlargement that lead to ventricular dilation and compensatory wall thickening (Jonker et al 2010).…”
Section: Regulatory Signals Associated With Birthmentioning
confidence: 99%
“…Among the chemical and mechanical factors that stimulate proliferation are arterial pressure load (Giraud et al 2005), angiotensin II ( Ang II ) (Sundgren et al 2003b), cortisol (Giraud et al 2006) and insulin-like growth factor-1 ( IGF-1 ) (Sundgren et al 2003a). Among those that suppress cardiac cell proliferation are tri-iodo-L-thyronine (T 3 ) (Chattergoon et al 2007), atrial natriuretic peptide (O'Tierney et al 2010b), and reduced cardiac systolic load (O'Tierney et al 2010a). …”
Section: Dynamics Of Cardiac Growth In the Fetusmentioning
confidence: 99%
“…To address this question, arterial pressures were reduced in fetal sheep and their cardiomyocytes examined (O'Tierney et al 2010a). Blockade of the angiotensin converting enzyme, which normally converts angiotensin I to angiotensin II, decreases fetal arterial pressure and thus systolic cardiac load.…”
Section: Decreasing Systolic Loadmentioning
confidence: 99%